ANALYSIS OF ELECTROMAGNETIC PERFORMANCE OF NOSE RADOME ON N219 AND NC212 AIRCRAFT - Fajar Ludihargi, Defanti
Airborne wireless application technology presents challenges for advancement of avionics technology. Therefore, high performance radome is required to support high transmission efficiency, low power reflection, minimum beamwidth changes, small main lobe shifts, and minimum increase of side lobe levels. Radome material and thickness have contribution to radome performance. The material shall have low dielectric constant and high mechanical strenght. Answering this challenge, two similar radomes in structure and material characteristics is analyzed in this thesis. N219 and NC212 aircraft radome are selected because of similarity of location on the aircraft nose and X-band operating frequency. N219 aircraft radome is measured at frequency 9.35, 9.40, and 9,45 GHz. Electromagnetic performance parameters are obtained in the form of transmission efficiency, beamwidth, beam deflection, and side lobe level. NC212 aircraft radome is measured at frequency 8.50, 9.50, and 10.6 GHz. Electromagnetics performance parameters obtained in the form of transmission efficiency and power reflection.Those performances are used to comply with DO-213 Change 1 and MIL-R-7705B. The N219 radome is a class B for transmission efficiency and meets the power reflection requirements based on DO-213 Change 1. The NC212 radome is a class A for transmission efficiency and meets the power reflection requirements based on DO-213 Change 1. Both radomes meet MIL-R-7705B transmission efficiency dan power reflection requirements. Althought it has similar arrangement of sandwiches and constituent material, the electromagnetic performances of those radomes are different.